Advances in etiology, pathophysiology, diagnosis, and management of lymphedema: a comprehensive review - Wu, Tianqi; Pu, Jun; Yao, Qi; Chen, Siying; Yao, Youheng; Chang, Suyan; Yang, Riyun; Shen, Jianhong (Frontiers in Medicine, 2025)
Lymphedema is a chronic disorder of impaired lymphatic transport that leads to fluid accumulation, fibrosis, and adipose expansion. It presents as primary disease, caused by genetic defects in lymphatic development, or as secondary disease after surgery, radiotherapy, infection, trauma, or malignancy. Recent studies have broadened the genetic basis of primary forms and clarified host and treatment-related risks for secondary forms. Mechanistic insights show that lymphatic stasis drives inflammation, fibrosis, and hypoxia, which remodel the microenvironment and reinforce lymphatic failure. Advances in imaging, including lymphoscintigraphy, indocyanine green lymphography, and magnetic resonance lymphangiography, enable earlier and more accurate diagnosis. Conservative treatment with complete decongestive therapy remains standard, while microsurgical techniques such as lymphaticovenous anastomosis and vascularized lymph node transfer expand options. Emerging pharmacologic strategies that target immune and fibrotic pathways show promise. This review summarizes current progress and highlights opportunities for precision interventions to improve outcomes.